Empowering Manager Performance: The Role of Heart Leadership in Boosting Job Satisfaction and Shaping Organizational Culture at PT Perkebunan Nusantara III (Persero) - Siregar, Darmansyah; Lubis, Zulkarnain; Rahmadani, Vivi Gusrini; Reza Aulia, Muhammad; Sinulingga, Mehaga Bastanta (Malikussaleh University, Aceh, Indonesia, 2024)
As the highest leader in the plantation and factory, the manager controls both the positive and bad aspects of the plantation and factory. Understanding how leaders act and behave regarding their Heart, emotional intelligence, and spiritual intelligence, as well as how this relates to Performance, remains a rare phenomenon. Emotional and spiritual intelligence are directly associated with leading from the Heart. To address the gap in our understanding, this study examines the effect of a heart-centered leadership style on the productivity of oil palm plantation company managers. Previously, there has been little research on how this style relates to Performance. Indonesia's palm oil companies are pretty advanced and have cornered the global market. Applying heartfelt leadership is one technique to boost manager performance. This calls for research into how a compassionate leadership style affects the productivity of oil palm workers. This research makes use of the partial least squares technique. This study found that managers' Performance was unaffected by heartfelt leadership but that it did affect team members' happiness and company culture. When managers are happy, they perform better, but company culture has little effect. Leadership with the Heart indirectly affects manager performance through job satisfaction.